Dibutylsulfide oxidation research the concentrated hydrogen peroxide solution by means of thermograms - L. R. Gaynullina; V. P. Tutubalina (Известия высших учебных заведений: Проблемы энергетики)
With the using of a thermographic method reaction of oxidation of dibutylsulfide in a noctane  95,6 %  concentrated  solution  of  hydrogen  peroxide  in  the  mixture  reactor  with  the propeller mixer is studied.It is established that dibutylsulfide oxidation by hydrogen peroxide in an ekvimoly-arny ratio 1:1 at a temperature of 80 °C proceeds before formation of a dibutilsulfoksid, and at a ratio 1:2 and at a temperature of 100 °C – to a dibutilsulfon.The increase in amount of hydrogen peroxide and temperature is followed by for-mation of sour products – the sulfoniyevykh and sulfonew acids.By method of a gas-liquid chromatography it is proved that during oxidation of dibutylsulfide by hydrogen peroxide his destruction doesn't happen.